The Use of Interactive E-Modules to Increase Students' Interest in Learning Entrepreneurship at SMK Telkom Pekanbaru - Loi, Kebetulan; Suarman, Suarman; Syahza, Almasdi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
The problem in this study is the low interest in student learning in entrepreneurship subjects. The problem that appears is the lack of student involvement and student interest in the learning process. This study aims to analyze students' entrepreneurial learning interests using interactive e-module teaching materials. This research was carried out at SMK Telkom Pekanbaru in class XII TKJ 1. This study used a type of experimental research with the One Group Pretest Posttest Design model. Data collection techniques using questionnaires and observations. The instruments in this study used questionnaire sheets and observation sheets. Data analysis techniques use descriptive analysis, t-test and Normality Gain (N-gain). The results showed that the use of interactive e-module teaching materials can increase students' interest in learning entrepreneurship. This can be seen from the difference in the level of interest in learning entrepreneurship students before and after the use of interactive e-modules shows from low to increase in very high categories. The use of interactive e-modules is effective in increasing students' interest in learning. Thus the conclusion of this study, there is an interest in learning student entrepreneurship with the use of interactive e-modules.